2011
DOI: 10.1104/pp.111.177030
|View full text |Cite
|
Sign up to set email alerts
|

Functional Incorporation of Sorghum Small Subunit Increases the Catalytic Turnover Rate of Rubisco in Transgenic Rice      

Abstract: Rubisco limits photosynthetic CO 2 fixation because of its low catalytic turnover rate (k cat ) and competing oxygenase reaction. Previous attempts to improve the catalytic efficiency of Rubisco by genetic engineering have gained little progress. Here we demonstrate that the introduction of the small subunit (RbcS) of high k cat Rubisco from the C 4 plant sorghum (Sorghum bicolor) significantly enhances k cat of Rubisco in transgenic rice (Oryza sativa). Three independent transgenic lines expressed sorghum Rbc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
112
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(119 citation statements)
references
References 41 publications
7
112
0
Order By: Relevance
“…The apparent catalytic neutrality of the tobacco S-subunit when assembled with heterologous L-subunits (Fig. 3) (24,29,30) contrasts with the recent success in shaping rice rubisco toward C 4 -like catalysis using heterologous S-subunits from C 4 sorghum (16). Similarly, structural changes to the S-subunit have improved Chlamydomonas rubisco catalysis (17).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The apparent catalytic neutrality of the tobacco S-subunit when assembled with heterologous L-subunits (Fig. 3) (24,29,30) contrasts with the recent success in shaping rice rubisco toward C 4 -like catalysis using heterologous S-subunits from C 4 sorghum (16). Similarly, structural changes to the S-subunit have improved Chlamydomonas rubisco catalysis (17).…”
Section: Discussionmentioning
confidence: 61%
“…At 25°C under ambient oxygen levels, the carboxylation efficiency (i.e., V C /K C 21%O2 ) of the C 4 -like 309 Ile-containing rubiscos in tob bid and tob flo-bid (145 mM −1 ·s −1 ) were poorer than the C 3 -like 309 Met-L 8 F S 8 t enzymes in tob pring and tob flo (150 and 161 mM −1 ·s −1 , respectively). Thus, because of the low CO 2 levels within (unstressed) C 3 chloroplasts (<10 μM), the faster C 4 -like enzymes probably provide no advantage to plant growth within a C 3 plant (at least at 25°C), as shown recently in rice (16). As modeled recently, optimal CO 2 concentrations required for C 4 rubisco are substantially higher (∼80 μM) (8), indicating that taking full advantage of a faster rubisco in a C 3 plant will require the combinatorial effect of a suitable CCM, for which a number of strategies are being pursued (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, expressing higher plant RbcS subunits in a Chlamydomonas reinhardtii mutant that lacks rbcS genes showed that RbcS makes a significant contribution to the Rubisco activity (Genkov et al, 2010). Expressing an RbcS from sorghum, a C4 plant, in rice, a C3 plant, resulted in increased catalytic turnover of Rubisco (Ishikawa et al, 2011).…”
mentioning
confidence: 99%
“…However, construction of such a cycle was still restricted by uncertainties in the expression, activity, stability, and regulation of all enzymes in this pathway. Recently, relocation of natural CO2-fixation pathways has (Kumar et al, 2009) Replaced the tobacco RuBisCO with cyanobacteria RuBisCO and observed significantly increased growth rate of tobacco under high concentration of CO2 2014 (Lin et al, 2014) Constructed a hybrid RuBisCO from different RuBisCO large and small subunits and studied its enzymatic properties - (Genkov et al, 2010;Ishikawa et al, 2011) Reported that over-expressing the sedoheptulose-1-7 bisphosphatase improves photosynthetic carbon gain and yield 2011 (Rosenthal et al, 2011) received much attention, as engineering natural CO2-fixing autotrophic microbes is usually difficult. In 2013, Mattozzi et al divided the 16 steps of the 3-hydroxypropionate cycle from Chloroflexus aurantiacus into four sub-pathways and expressed each sub-pathway in Escherichia coli (Mattozzi et al, 2013).…”
Section: Design and Relocation Of Co2-fixation Pathwaymentioning
confidence: 99%